Codigestão anaeróbia de lixiviado de aterro sanitário e glicerol - Silva, Camila Zanoni (2017)
The present study aims to evaluate the efficiency of anaerobic codigestion of landfill leachate in association with glycerol, obtained from biodiesel production. The substrates (leachate and glycerol) were characterized by physicochemical parameters. The assays, used to evaluate anaerobic codigestion, were carried out in batch reactors, connected to eudiometers that measured biogas volume. At the same time, replicas destructive were developed as testimony of the reactors. Thus, an experimental planning tool was used to determine the optimal sizing parameters for anaerobic codigestion and significant factors for anaerobic codigestion were determined by Plackett and Burman delineation. Subsequently, the Rotational Central Composite Design applied to the Response Surface Methodology was used to establish the optimal conditions for the codigestion process. Firstly, four independent variables were analyzed: time (30, 40 and 50 days), pH (6, 7, 8), leachate + glycerol concentration (99% + 1%, 95% + 5% and 91 + 9 %) and food/ microorganism ratio (0.5, 1.2, 1.9 g COD/g of VSS). Three influential variables were evaluated after the definition of variables that influenced codigestion process: time (14, 18, 24, 30 and 34 days) leachate + glycerol concentration (93.4%+6.6%, 90%+10%, 85%+15%, 80+20% and 76.6+23.4) as well as food/ microorganism ratio (0.5, 0.6, 0.7, 0.8 g COD/g of VSS). By optimizing the anaerobic codigestion process, it was possible to increase glycerol concentration and decrease reactors operating time as well as obtain feasible results to remove COD (96%) and methane production (205 L CH4/m³).